Prevalence and socioeconomic factors associated with smoking in people living with HIV by sex, in Recife, Brazil - Joanna d'Arc Lyra Batista; Maria de Fátima Pessoa Militão de Albuquerque; Ricardo Arraes de Alencar Ximenes; Demócrito de Barros Miranda-Filho; Heloisa Ramos Lacerda de Melo; Magda Maruza; Libia Vilela Moura; Eduardo Jaime Seara Pinto da Costa Ferraz; Laura Cunha Rodrigues (Associação Brasileira de Pós-Graduação em Saúde Coletiva, 2013)
Introduction: Smoking is the leading cause of preventable death in the world. The prevalence of smoking is higher in people infected with HIV than in the general population. Although it is biologically plausible that smoking increases the morbidity and mortality of people living with HIV/AIDS, few studies in developing countries have analyzed the determinants and consequences of smoking in HIV infected people. Objective: To estimate the prevalence of smoking and identify the socioeconomic factors associated with smoking and smoking cessation in patients with HIV by sex. Methods: A cross-sectional study was conducted with baseline data, obtained from an ongoing prospective cohort study of patients with HIV attending two referral centers in Recife, Northeast Region of Brazil, between July 2007 and October 2009. Results: The prevalence of current smoking was 28.9%. For both sexes, smoking was independently associated with heavy alcohol drinking and marijuana use. Among women, smoking was associated with living alone, not being married and illiteracy; and among men, being 40 years or older, low income and using crack. Compared with ex-smokers, current smokers were younger and more likely to be unmarried, heavy drinkers and marijuana users. Conclusions: It is important to incorporate smoking cessation interventions for the treatment of heavy alcohol drinkers and marijuana users with HIV/AIDS, which may increase life expectancy and quality of life, as smoking is related to risk of death, relapse of tuberculosis, and non communicable diseases.